A preliminary evaluation of a client-centred prompting tool for supporting everyday activities in individuals with mild to moderate levels of cognitive impairment due to dementia. (April 2021) - Harris, Nigel; Boyd, Hazel; Evans, Nina; Cheston, Richard; Noonan, Krist; Ingram, Thomas; Jarvis, Aron; Ridgers, Jessica
Objectives: Technology-based prompting has the potential to support people with dementia to complete multistep tasks in the home. However, these devices can be complex to use. This paper reports a feasibility trial of a personalised touchscreen digital prompter designed for home use. Methodology: A tablet-based prompter suitable for people living with dementia was developed, along with a detailed guidance manual. Carers loaded instructions for completing the task onto the prompter, and the person with dementia then used the tablet independently to complete a task. Eleven couples used the prompter 'out-of-the-box' with no support other than a guidance manual. Results: The majority of participants with dementia could follow the steps on the prompter, and carers were able to breakdown and load tasks onto the prompter. Eight couples used the prompter successfully to complete goals that they had identified in advance. These included preparing simple snacks and using a TV remote control. Successfully achieving goals was associated with more frequent use of the prompting screen on more days, but not higher levels of editing or previewing of tasks. Conclusion: The study provides the preliminary evidence that family caregivers can use a touchscreen tablet, software and manual package to identify specific tasks and break these down into steps and that people living with dementia can then follow the prompts to complete the tasks. This potentially represents an important advance in dementia care. Further testing is required to establish efficacy and to identify any factors that impact on outcomes.